An Unusual 3D Zinc‐Organic Framework Constructed from Paddle‐Wheel‐Based Carboxylate Sheets Bridged by Acetate Ions. Issue 11 (6th June 2016) - Saffon‐Merceron, Nathalie; Barthélémy, Marie‐Claire; Laurent, Christophe; Fabing, Isabelle; Hoffmann, Pascal; Vigroux, Alain
Abstract: A zinc‐2, 6‐naphthalenedicarboxylate metal‐organic framework, (H2 NEt2 )[Zn2 (AcO)(NDC)2 ]· n DEF (1 ) (DEF = N, N ‐diethylformamide, AcO = acetate), was solvothermally synthesized in the presence of small amounts of acetic acid and characterized by single‐crystal and powder X‐ray diffraction and thermogravimetric analysis. Compound1 is an anionic 3D paddle‐wheel MOF, in which the zinc‐naphthalenedicarboxylate sheets are linked together by bridging acetate ions. Compound1 exhibits large square channels (13 × 13 Å), which contain DEF molecules and, alternatively, charge‐balancing diethylammonium cations in situ generated by the hydrolysis of DEF under the solvothermal conditions used. The anionic host framework of1 is unstable upon removal of guest DEF molecules suggesting that host‐guest hydrogen bond interactions are crucial for maintaining the structural integrity of this compound. Abstract :